Transformations in Teacher Identity According to PIBIDers (PERcursos Linguísticos, 2021)
This article aims at discussing the experience of tem undergraduate students from a Language Course in a public university in order to understand the meanings They (re)constructed with their participation in the Institutional Scholarships Program for Teaching Internship (PIBID), sub-project English.A qualitative research (Flick, 2009) was, therefore carried out which, after contextualizing the teaching of the English language in Brazil ((Celani, 2010; Leffa, 2016; Szundy, 2017), has its theoretical underpinnings on recent elaborations on language teacher education (Celani, 2016; Silvestre, 2017) and the role of narratives to bring about reflections during this process (Barcelos; Ruohotie, 2018; Mello, 2020), as well as on language teacher identities  (Barkhuizen,2017; Freitas; Velasques,2018; Reichmann; Romero, 2019). The results of this research confirm the Program potential to intervene for identity transformations, since the collaborators sayings could reveal their learnings which were socially constructed while developing the works proposed. These learning especially resulted through the interactions with peers, public school students, teachers and educators from the University. In this perspective, one may endorse that PIBID has led to the ressignification in the identity of future teachers of English, which may set the path for qualitative changes in teaching and learning practices for the public school.